From Natural Resources to the Knowledge Economy : Trade and Job Quality - de Ferranti, David; Perry, Guillermo E.; Lederman, Daniel; Maloney, William E. (Washington, DC: World Bank, 2013)
The study questions whether, after a decade of remarkable progress in trade reform, Latin America and the Caribbean really integrates into the global market, offering a promising rapid growth, and good jobs for its workers. For despite the incidence of the loosely called "knowledge economy", the concern prevails that most countries' rich natural resources, still are the determining factor for exports. Policy recommendations include fostering openness to trade, market access, and foreign direct investment flows, in addition to building human capital, institutions, and public infrastructure, without disregarding the natural advantages. To this end, policymakers should aim at developing educational systems that provide quality education, focused on lifelong learning, and training activities to build human capital. Emphasis should follow on research and development (R&D) incentives, and innovations systems, arguing that countries should experiment with taxation incentives, and subsidies to promote both private, and public investments in R&D, (dependent on the institutional capacity of governments to enforce tax laws, and monitor the quality of investments). Moreover, evidence in this report, suggests that information, and communications technology (ICT) can reduce coordination costs, enabling an effective industrialization, and market access.